Worldviews and the construal of suffering from depression. (28th March 2019) - Palitsky, Roman; Sullivan, Daniel; Young, Isaac F.; Dong, Sheila
Abstract: We examine how worldview differences affect the construal of depression. Two suffering construals are identified: redemptive construals, which emphasize the growth‐oriented teleological purpose of depression, and biomedical construals, which emphasize a restorative teleology whereby depression should be pharmacologically treated to return individuals to normal functioning. Due to their assumptions about human nature, we anticipated that humanistic and normativistic worldviews would be associated with redemptive and biomedical construals, respectively. Four studies examined whether these associations are (a) cross‐sectionally evident, (b) causal in nature, and (c) impacted by perceived risk for depression. Humanism was positively and causally associated with redemptive construals; this association was strengthened by perceived personal risk for depression. Normativism was consistently positively associated with biomedical construals, except when participants anticipated an assessment of their risk for depression. Furthermore, in one study (Study 1B), normativism was associated with fear‐based stigma of a depressed individual (being more likely to view this person as dangerous because of their condition). These results provide initial evidence for our novel theoretical framework, which, in distinction to prior theory and research, highlights the importance of (a) assessing worldview beyond political orientation in explaining depression attitudes and (b) lay teleologies, as distinct from "folk etiologies, " of mental illness. Redemptive and biomedical construals have different implications for phenomena such as treatment adherence and stigma.